2012
DOI: 10.1007/s10509-011-0973-6
|View full text |Cite
|
Sign up to set email alerts
|

GPS-TEC variations during low solar activity period (2007–2009) at Indian low latitude stations

Abstract: The paper is based on the ionospheric variations in terms of vertical total electron content (VTEC) for the low solar activity period from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 46 publications
4
10
0
Order By: Relevance
“…Using the formula 3.5 in Park (1972) . This is in good agreement with ionospheric total electron contents (TEC) measured using Global Positioning Systems (GPS) based measurements over Indian low latitude stations (Chauhan and Singh, 2010;Kumar et al, 2012). Kumar et al (2012) reported that TEC over low latitude Indian stations varies between 10 TECU and 50 TECU.…”
Section: Whistler-lightning Connectionssupporting
confidence: 85%
See 3 more Smart Citations
“…Using the formula 3.5 in Park (1972) . This is in good agreement with ionospheric total electron contents (TEC) measured using Global Positioning Systems (GPS) based measurements over Indian low latitude stations (Chauhan and Singh, 2010;Kumar et al, 2012). Kumar et al (2012) reported that TEC over low latitude Indian stations varies between 10 TECU and 50 TECU.…”
Section: Whistler-lightning Connectionssupporting
confidence: 85%
“…This is in good agreement with ionospheric total electron contents (TEC) measured using Global Positioning Systems (GPS) based measurements over Indian low latitude stations (Chauhan and Singh, 2010;Kumar et al, 2012). Kumar et al (2012) reported that TEC over low latitude Indian stations varies between 10 TECU and 50 TECU. The International Reference Ionosphere (IRI) modeled TEC over Indian stations also compares well with our computed columnar ionospheric electron contents using observed whistlers (Chauhan and Singh, 2010;Kumar et al, 2012).…”
Section: Whistler-lightning Connectionssupporting
confidence: 85%
See 2 more Smart Citations
“…The ionosphere, being a complex physical system, exhibits different features like diurnal, seasonal, and spatial variability. The distribution and characteristics of TEC over low, mid, and high latitudes have been investigated by several authors (Rama Rao et al 2006;Yizengaw et al 2007;Liu et al 2008;Bagiya et al 2009;Jain et al 2011;Zou et al 2011;Sojka et al 2012;Kumar et al 2012). The latitudinal variation of the TEC is mostly dictated by the phenomenon of EIA (Kumar and Singh 2009;Venkatesh et al 2011).…”
Section: Introductionmentioning
confidence: 99%